FAKTOR YANG MEMPENGARUHI KEJADIAN RETENSIO PLASENTA DI RSUD dr. R. GOETENG TAROENADIBRATA 2 PURBALINGGA TAHUN 2009 - Etika Dewi Cahyaningrum; Akmilul Qurrotul Aini (Universitas Harapan Bangsa Purwokerto, 2010)
Background : Retained placenta is a complication that can occur on the thirdstage of labor. Based on the results of pre-survey conducted on December 3, 2009in dr. R. Goeteng Taroenadibrata there are 90 people (10.4%) experienced aretained placenta of 862 spontaneous labor.Objective : Know the description of factors that affect the incidence of retainedplacenta in dr. R. Goeteng Taroenadibrata 2009.Method : This research is quantitative descriptive retrospective approach.Research uses secondary data from the register book and a medical record of thepatient.Result : The majority of respondents either with or without a retained placentaretained placenta were in the age group 20-35 years. The majority of respondentseither with or without a retained placenta retained placenta are at parity groupmultiparas. The majority of respondents either with or without a retained placentaretained placenta were in the group do not have a history of previous uterinecurettage. There are differences between respondents with and without retainedplacenta retained placenta retained placenta that a majority of respondents with ahistory of previous retained placenta retained placenta, while respondents withouta majority did not have a history of previous retained placenta. The majority ofrespondents either with or without a retained placenta retained placenta were inthe group do not have a history of placenta previa.Conclusion : There is equality of outcome between the mother retained placentaand without retained placenta in age, parity, history of previous uterine curettage,and a history of placenta previa, and there are differences in the results of thefactor prior history of retained placenta. Keyword : Retained placenta, age, parity, history of previous uterine curettage, ahistory of previous retained placenta, placenta previa history.